Keyword-Based Model of Teaching English for Adult Learners - Susi Ekalestari; Sri Wulan; Dewi Nurmala; Nurhasanah Nurhasanah; Tristi Ananda (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study discusses the keyword-based model in learning English to for adult learners who in fact have little free time due to various activities but require the ability to communicate in English. Researchers are triggered to make this model because of their weakness in English, so they often have problems communicating with foreign partners. The research method adopted in this study is a qualitative method with descriptive analysis. "Descriptive analysis is an analysis used to analyze data by describing the data that has been collected as it is without intending to make conclusions that apply to the public or generalizations." (Sugiono. 2016). The instrument used for data collection in this study is a questionnaire. The model's effectiveness test is also carried out by looking at the increase or decrease in the respondents' English understanding of English language. The respondents of this study are lecturers and officers at the Islamic University of North Sumatra which are determined using purposive sampling. The findings of this study is an effective and efficient keyword-based model for adult learners because with a keyword-based model, learners do not need a long time to spend in learning English, so it does not cost too much considering they have little free time.